Tanzania : Agricultural Sector Risk Assessment - Arce, Carlos E. (World Bank, Washington, DC, 2015)
This study aims to achieve a better understanding of the agricultural risk and risk management situation in Tanzania with a view to identifying key solutions to reduce current gross domestic product (GDP) growth volatility. For the purpose of this assessment, risk is defined as the probability that an uncertain event will occur that can potentially produce losses to participants along the supply chain. Persistence of unmanaged risks in agriculture is a cause of great economic losses for farmers and other actors along the supply chains (for example, traders, processors, and exporters), affecting export earnings and food security. The agricultural sector risk assessment is a straightforward methodology based on a three-phase sequential process. Phase analyzes the chronological occurrence of inter-seasonal agricultural risks with a view to identify and prioritize the risks that are the drivers of agricultural GDP volatility. This report contains the findings and recommendations of the first phase and includes the identification, analysis, and prioritization of major risks facing the agricultural sector in Tanzania, as well as recommendations regarding key solutions. Chapter one gives introduction and context. Chapter two contains an overview of the agricultural sector and its performance, as well as a discussion of key agro-climatic, weather, and policy restrictions and opportunities. Chapter three includes an assessment of major risks (that is, production, market, and enabling environment risks) facing key export and food crops. Chapter four presents an estimate of historical losses due to realized production risks and a correlation of such losses with production volatility. Chapter five provides insights into the exposure to risks by different stakeholders and their actual capacities, vulnerabilities, and potential to manage agricultural risks. Chapter six presents a risk prioritization by different supply chains and discusses the possible solutions, as well as specific recommendations for the agricultural sector development program (ASDP).